2019
DOI: 10.4314/njbas.v26i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Levels and human health risk assessment of persistent organics, metalloid and heavy metals in fish

Abstract: Concentrations of Persistent organics (Polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), metalloid (As) and heavy metals (Fe, Zn, Mn, Cu, Ni, Cd. V, Cr, Pb, Hg) were measured in fish (Clarias gariepinus) samples collected from selected stations (S1, S2 and S3) along the stretch of Ovia River, Southern Nigeria, to assess the potential risks to humans consuming fish from the river. Acenaphthylene (AcPY), PCB 18 and iron (Fe) were the most dominant residues with mean concentrations rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Anaero-Nweke et al [25] in a study of bioaccumulation of heavy metals in tissues of Tympanotonus fuscatus had reported EDI range of 6.57-8.81 mgkg −1 above FAO/WHO [26] permission tolerable daily intake of 0.25 mgkg −1 for Pb and EDI values of 0.01-0.07 mgkg −1 within FAO/WHO [26] permissible tolerable daily intake of 0.07 mgkg −1 for Cd. Tongo and Ezemonye [18], had reported EDI values of 0.138-0.200 mgkg −1 in Figure 3. Estimated daily intake of the periwinkles is presented in the study area.…”
Section: Exposure Assessment (Estimated Daily Intake (Edi))mentioning
confidence: 99%
“…Anaero-Nweke et al [25] in a study of bioaccumulation of heavy metals in tissues of Tympanotonus fuscatus had reported EDI range of 6.57-8.81 mgkg −1 above FAO/WHO [26] permission tolerable daily intake of 0.25 mgkg −1 for Pb and EDI values of 0.01-0.07 mgkg −1 within FAO/WHO [26] permissible tolerable daily intake of 0.07 mgkg −1 for Cd. Tongo and Ezemonye [18], had reported EDI values of 0.138-0.200 mgkg −1 in Figure 3. Estimated daily intake of the periwinkles is presented in the study area.…”
Section: Exposure Assessment (Estimated Daily Intake (Edi))mentioning
confidence: 99%